Expression of CD 68, CD 45 and human leukocyte antigen-DR in central and peripheral giant cell granuloma, giant cell tumor of long bones, and tuberculous granuloma: An immunohistochemical study - Anoop Kumar; Herald J Sherlin; Pratibha Ramani; Anuja Natesan; Priya Premkumar (Wolters Kluwer Medknow Publications, 2015)
Background: Multinucleated giant cells (MNCs) form an integral part of numerous bone and soft tissue tumors, tumor-like lesions and are often associated with granulomas of immunological and nonimmunological origin. The presence of various types of giant cells depends on the lesions in which they are present which are difficult to be diagnosed under routine histological techniques. Immunohistochemistry can be used for a better diagnosis and understanding of the origin of various giant cells using various markers of immune response like human leukocyte antigen-DR (HLA-DR) and those expressed on monocytes and macrophages like CD 68 and leukocyte common antigen (LCA). Materials and Methods: The study group consisted of 10 cases of giant cell tumor (GCT) of long bones, tuberculous granuloma, and giant cell granuloma to evaluate and analyze the expression pattern of LCA, CD 68, and HLA-DR in various giant cell lesions. Results: Strong expression of CD 68 was observed in 80% of the lesions, strong and moderate expression of CD 45 observed in 70% of the lesions among and within the groups. In contrast, HLA-DR demonstrated negative expression in 80% of cases except for tuberculous granuloma where all the 10 cases showed moderate to strong immunoreactivity. Conclusion: CD 68 and CD 45 expression was found in central giant cell granuloma, peripheral giant cell granuloma and GCT, suggesting the origin from mononuclear phagocyte system and considering their clinical behavior of osteoclast type. High expressivity of HLA-DR in tuberculous granulomas which is an essential factor for presentation of the microbial antigen to CD 4 helper cells thus reassuring the fact that they are up-regulated in response to infection.